Demand- and supply-side factors associated with the use of contraceptive methods in Pakistan: a comparative study of demographic and health surveys, 1990-2018 - Sadia Jabeen; Adnan Rathor; Maria Riaz; Rubeena Zakar; Florian Fischer (BMC, 2020)
Abstract Background A remarkable decline in fertility rates has been observed in many countries, with a primary determinant being an increase in the use of contraceptives. However, the birth rate in Pakistan is still higher compared to the other countries of the region. Therefore, this study aims to assess the effect of demand- and supply-side factors associated with the use of contraceptive measures in Pakistan. Methods Secondary data analysis of four data series of the Pakistan Demographic and Health Surveys (PDHS 1990-1991, 2006-2007, 2012-2013 and 2017-2018) were used. The data includes ever-married women aged 15-49 years who had given birth in the previous five years and participated in the family planning module of the PDHS. A total of 25,318 women were included in the analysis. Data were analysed by investigating the associations between independent variables (demand- and supply-side factors) and the use of contraceptive measures through unadjusted odds ratios (OR) and adjusted OR (AOR). Results The results among demand-side factors indicated that in 2012-2013, women without media exposure were less likely to use contraceptives and the trend remains almost constant for 2017-2018 (AOR = 0.664, 95% CI 0.562-0.784) in 2012-2013 and (AOR = 0.654, 95% CI 0.483-0.885) in 2017-2018. However, they still show a lower likelihood of using contraceptives without media exposure. The results among supply-side factors indicated that absence of transport (2012-2013) and limited visits by family planning workers over the previous 12 months (2006-2007, 2012-2013 and 2017-2018) remained significant factors for not using contraceptive methods. Conclusions The results of the study indicate that certain demand- and supply-side factors are associated with the use of contraceptive measures in Pakistan. It highlights the need for the provision of family planning resources and further structural factors, particularly in remote areas.